Aplikasi Penyewaan Alat Berat Pada PT. UNITED TRACTORS Pontianak Berbasis Desktop - Nanda Diaz Arizona; Hadi Rabianto (Jurnal Sistem Informasi Akuntansi, 2020)
PT United Tractors Pontianak, is still done manually, starting from recording to storing other data relating to the rental process, so that it is possible that during the process of error occurs in recording, inaccurate reports made and delays in searching the necessary data. The research method is research and data collection methods are observation, interview, and literature. Computerized system is the best solution to solve the problems that exist in PT United Tractors Pontianak, as well as with a computerized system an effective and efficient activity can be achieved to support the activities of PT United Tractors Pontianak. Therefore a computerized system is better than a manual system, so that it runs more effectively and efficiently and the rental system is now more conducive compared to the previous system.